PHYSICAL – WATER A CLAYEY OXISOL AFTER MECHANICALLY INDUCED COMPRESSION - Amaral, K.F.S.; Rosa, H. A.; Giese, V.; Montiel, C.B.; Brondani, S. T.; Secco, D. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Soil compaction is one of the main factors that change the quality of soil and crop growth. The experiment will be conducted to evaluate the effect of compression on the physical - soil water. The completely randomized design (CRD) will be composed of 4 treatments and 5 repetitions (T1 - without compression; T2 - four passed with tractor, T3 - past six with tractor and T4 - eight strides with tractor) compression was held on the data collect. The samples submitted to tensions 33 and 100 kPa Richards pressure chamber. To obtain the values ​​of the total porosity of the soil, samples were prepared and packaged in plastic trays, and saturated in water. Data were submitted to analysis of variance (ANOVA) and treatment means were compared by the test "Tukey 5%" of significance, the Assistat Software. In relation to Pt, at the depth of 10-20 cm T3 treatment had lower values. It is concluded that the amount of pasts of a tractor, in a clay latosol, altered the physical-water characteristics of the soil, except for the microporosity. The 10-20 cm layer presented the highest statistical differences, with changes in Pt, Macroporos and DTA values.